Система неперервної освіти в Україні та Великій Британії - Орос Ільдіко; Orosz Ildikó; Oros Ildiko (Видавництво «Код», 2023)
Резюме. Неперервне навчання людини передбачає професійний розвиток особистості, який відображає процес її підготовки до трудової діяльності чи перепідготовки в разі зміни професії, а також підвищення кваліфікації з метою поглиблення професійних знань і розширення профмайстерності.

Abstract. Continuous training of a person involves the professional development of an individual, which reflects the process of his preparation for work or retraining in the event of a change of profession, as well as professional development in order to deepen professional knowledge and expand professional skills. On the basis of a comparative analysis of the development of adult education and their continuing education in Great Britain and Ukraine, similar approaches to the organization of professional training of the adult population and features of the development of adult education have been identified, and on this basis, progressive ideas of the British experience on the outlined problem have been identified. We believe that in order to implement state policy in the field of adult education in Ukraine, it is expedient to implement the progressive ideas of the British experience in adult education outlined by us in the organization of the educational process of education of the adult population of Ukraine and to determine the directions of their creative implementation in Ukraine. It has been proven that one of the ways to solve the problem of improving continuous education in the conditions of Ukraine's integration into the European and world educational space, rapid processes of globalization and internationalization, ensuring the mobility of human capital, and the development of the information society is not only turning to the best examples of domestic pedagogical science, but and taking into account the general trends of the European experience of adult education throughout life, the results of international research, progressive ideas of foreign experience. In this context, the study of Great Britain's experience in building a system of continuous education is of great interest and can become an important source of comprehensive understanding and creative use of its positive ideas.
Continuous education system in Ukraine and Great Britain
https://opac3.brff.monguz.hu/hu/record/-/record/bibBRF00011820
https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-5
Keywords: неперервна освіта; Україна; Велика Британія; прогресивні ідеї; освіта дорослих